TRANSFORMATION OF THE WORLD ECONOMIC SYSTEM AND ITS IMPACT ON STATE REGIONAL ECONOMIC POLICY IN UKRAINE: NEW CHALLENGES AND THREATS - ZVARYCH, Ihor; ZVARYCH, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
For economic science, the process of globalization, globalization transformations and shifts is connected with the formation of a single world economic system that functions according to general rules. The beginning of the twenty-first century is marked by the regionalization of the political space of our country. Regionalism is increasingly asserting its rights as one of the most influential concepts of Western democracy. Within the framework of the European Union, there is a concept of "Europe of Regions". Researchers pay attention to regional processes in the European space, paying tribute to the trends that are constantly developing there. Regionalism can be "administrative", and in some cases it acquires a political character. Regionalism with a noticeable political accent, in which separatist motives play a leading role, is quite relevant for Ukraine. In our opinion, regionalism is not a unequivocally negative or destructive phenomenon, it has a rather significant potential of constructivism. This phenomenon is heterogeneous and ambiguous in the modern political history of various states. There is a need to develop a comprehensive program of state regional policy, taking into account the processes of political modernization and integration of Ukraine into the European political space.
Keywords: globalization; transformation; economic system; regionalism; political space; state; administrative; management